2021
DOI: 10.1186/s41155-021-00198-5
|View full text |Cite
|
Sign up to set email alerts
|

The association between problematic Internet use, eating disorder behaviors, and well-being among Palestinian university students

Abstract: Objectives The current study aimed to test the correlation between problematic Internet use, eating disorder behaviors, and well-being among Palestinian university students. Methods To examine the relationship between the study variables, a correlational study was conducted. The geographical representation of the study sample showed that 48.1% of participants were from urban populations, 48.1% were from rural villages, and 3.8% were from internally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Nowadays, people pay a lot of heed to celebrities and influencers promoting unreasonable and unrealistic beauty standards, while spending hours and hours on social media. (33) This leads to dissatisfaction with one's own body, therefore, contributing to disordered eating behaviors. On the one hand, the internet may provide a haven for those unhappy with their body shape and size.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, people pay a lot of heed to celebrities and influencers promoting unreasonable and unrealistic beauty standards, while spending hours and hours on social media. (33) This leads to dissatisfaction with one's own body, therefore, contributing to disordered eating behaviors. On the one hand, the internet may provide a haven for those unhappy with their body shape and size.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has also been associated with poor academic outcomes among students, including lower academic grades, missed assignments, and academic disqualification [8]. In general, students with PIU reported poor health behaviors and can lead an unhealthy lifestyle [8][9][10][11]. Studies revealed that PIU significantly increased social anxiety [12], eating disorders [9,11], problematic thoughts [13], suicidal ideation and attempt, social isolation, subjective distress [9,10,14,15], and less healthprotective behaviors [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…In general, students with PIU reported poor health behaviors and can lead an unhealthy lifestyle [8][9][10][11]. Studies revealed that PIU significantly increased social anxiety [12], eating disorders [9,11], problematic thoughts [13], suicidal ideation and attempt, social isolation, subjective distress [9,10,14,15], and less healthprotective behaviors [9,11].…”
Section: Introductionmentioning
confidence: 99%